Dinamiškųjų lokatyvinių sakinių nominalizacija lietuvių ir anglų kalbose - Valeika, L. (Kalbotyra, 1977)
The article deals with nominalising transformations of dynamiclocative sentences (e. g. John has returned home). The comparison of Lithuanian and English evidence has shown Lithuanian derivatives to be more rich semantically and free syntactically. In Lithuanian verbal derivatives are marked aspectually, whereas in English they are not. In Lithuanian the expanded adjunct of a locative nominal may be used both in preposition and postposition, in English it is used in postposition only.